Hotel Resort Paropo With Neo Vernacular Approach - Uci Utari; Wahyu Utami (International Journal of Architecture and Urbanism, 2020)
Lake Toba is the largest lake in Indonesia, even in Southeast Asia. Lake Toba has excellent potential as a tourism area development in North Sumatra. On the outskirts of Lake Toba, especially Paropo, there are still many who do not have facilities for tourists, the large number of tourists who come to Paropo causes the Paropo area to need supporting facilities such as resort hotels as supporters of North Sumatra tourism development. Resort hotels are hotels located in tourist attractions, such as mountains, beaches, and lakes. The design of the Paropo resort hotel applies the Neo vernacular architectural concept. The problem with this design is "how to apply the neo vernacular architectural concept to the design of a resort hotel." The purpose of applying the concept of Neo vernacular architecture in buildings is one of the efforts so that it is inseparable from the surrounding culture and can also introduce regional culture to the tourists who come. Designing this resort hotel uses qualitative methods. This resort hotel brings the theme of Neo vernacular architecture that combines traditional Dairi/Pak-Pak architecture with modern architecture, where physical elements are applied/changed but also non-physical items such as cultural values, mindset, beliefs, layout, religion, etc. into the form of buildings and site design. The benefit of designing this resort hotel is the creation of resort hotels that can still preserve the elements of local culture with a layer of modernization and, if built, can develop the tourism area of ​​Paropo to attract tourists.